Gamma irradiation effect on properties of modified graphene doped PVA nanocomposite films - Thaises Lima; Filipe Diniz; Elmo Araújo; Patrícia Araújo (Polímeros)
Abstract Gamma radiation effects on extrinsically electrical semiconducting polymer nanocomposite films of poly(vinyl alcohol) (PVA) and 0.5 wt% histidine-modified reduced graphene oxide (H-RGO) filler were evaluated. Thermogravimetric analysis showed thermal degradation stages of the films and UV-Vis analysis allowed the study of optical parameters. Optical band gap energy (Eg) of PVA was shifted from 6.20 to 3.76 eV with the addition of H-RGO filler into the polymer matrix, while the electrical conductivity changed from 10-11 (isolator) to 10-6 (semiconductor) S/cm and PVA/H-RGO nanocomposite reached 10-4 S/cm at 25 kGy gamma-radiation dose. PVA/H-RGO nanocomposite films are promising in a wide range of potential applications, such as bio and chemical sensors, catalysis, and active layers for optoelectronic devices.